Farmer's Perceptions of Sustainable Land Management Practices in Sekota District, Northeastern, Ethiopia - Asresu, Melaku; Tarekegn, Chalachew (International Journal on Food, Agriculture and Natural Resources, 2025)
Land degradation is a significant threat to agricultural productivity and economic growth in Ethiopia. Despite the promotion of sustainable land management practices (SLMPs) by government and development agencies to enhance agricultural productivity, the perception level among smallholder farmers remains low. This study aimed to analyze farmers’ perceptions on SLMPs and practices utilized by farmers. Data were collected from 267 randomly selected households using a multistage sampling technique, which included an interview schedule, key informant interviews, and focus group discussions from three sample kebeles in Sekota district during in 2024 production season. Descriptive statistics was used for analyzing quantitative data while qualitative data was analyzed by narrations, interpretation, and conceptual generalization. The most common SLM practices included crop rotation (30.71%), livestock manure (25.84%), integrated methods (20.97%), inorganic fertilizer (17.6%), and compost (4.87%). Our study shows farmers had positive perception index scores for SLMPs, with livestock manure (4.78), livestock manure + inorganic fertilizer (4.14), compost (4.12), and crop rotation (3.99) respectively, although lack of transportation, high price inflation, and labor-intensive were mentioned as the major factors in livestock manure, inorganic fertilizer, and compost respectively. The majority (78.3%) of farmers believed that soil fertility would continue to decline, while 12.7% perceived it would remain unchanged, and 9% perceived it would improve. The finding of the study shows that almost all farmers of the study area had a good perception on the land management practices, as well as the causes and consequences of soil degradation. The major causes of soil degradation perceived by farmers were over-cultivation without fallowing, soil erosion, the slope of the land and poor tillage practices. Whereas declining land productivity, declining crop production, land becoming out of cultivation, hunger and migration, and poverty were the major consequences of soil degradation in the study area. Therefore, increasing farmers’ perception about land degradation risks, enhancing extension service, improving access to training,  improving land productivity per unit area, and addressing barriers specific to each practice are essential to promoting sustainable land management in the study area